Abiotic degradation behavior of polyacrylonitrile-based material filled with a composite of TiO2 and g-C3N4 under solar illumination. (July 2022) - Zhong, Yunjin; Chen, Haixiang; Chen, Xiufang; Zhang, Bingying; Chen, Wenxing; Lu, Wangyang
Abstract: As some of the most promising alternatives to traditional non-degradable materials, photodegradable materials have advantages of environmental benignity and rapid degradation under simple conditions. In this work, nontoxic TiO2 and cost-effective g-C3 N4 have been compounded in a weight of 9:1 to form a photocatalytic additive with high activity. A 25 wt% loading of this photocatalytic additive has been incorporated into the polyacrylonitrile (PAN) by centrifugal electrospinning to prepare an abiotic degradable PAN material. Our results showed that the PAN chain could be almost fully degraded within 90 h in an aqueous medium under simulated sunlight in the absence of microorganisms. Product analysis implied that degradation of the PAN chain mainly involved the breaking of –CN and C–C bonds by radicals, followed by oxidation of terminal groups to carboxyl and gradual mineralization to CO2 and H2 O. This design strategy may provide new insight for the production and degradation mechanism of photodegradable polymer. Graphical abstract: Image 1 Highlights: A PAN material can be abiotic biodegraded completely under sunlight. The heterojunction structure of TiO2 /g-C3 N4 greatly improved photocatalytic activity. A new opinion to solve microplastic pollution in water environment is proposed. The photodegradation mechanism of PAN is systematically analyzed.